PENGARUH PEMASARAN DIGITAL DAN CITRA MEREK TERHADAP MINAT BELI MAHASISWA UNIVERSITAS KRISNADWIPAYANA DI TOKOPEDIA - Agung Rizky Kautsar; Iwan Kurniawan Subagja (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2024)
This research aims to find out whether influence between digital marketing and brand image on purchase interest. This research was conducted on economics Students faculty of 2019. The research sample and the sampling technique used purposive sampling. Data analysis uses multiple linear regression. The results of the analysis show that digital marketing influences purchasing interest and has a significant relationship, the brand image variable has a significant influence on purchasing interest. Digital marketing and brand image variables have a significant influence on purchasing interest.